PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN KONAWE SELATAN - Wa Ode Hasniati; Aidin Hudani Awasinombu; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this study was to examine and explain the influence of leadership style, work motivation and work discipline both partially and simultaneously on employee performance at the Population Control and Family Planning in South Konawe Regency. This research approach is quantitative using survey methods and explanatory research design. The data was collected by cross-section using an instrument in the form of a questionnaire. The population of this study were employees of the Population Control and Family Planning Office of South Konawe Regency, by using the method of determining respondents by census, so that the sample size was set at 84 employees. The analytical tool used is the Multivariate Regression Analysis.The results showed that the leadership style had a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Finally, leadership style, work motivation and work discipline simultaneously have a significant effect on employee performance. From the results of these studies it can be concluded that the better the leadership style is applied, the higher the work motivation of the employees and the better the level of work discipline applied by employees will be able to improve employee performance for the better.The purpose of this study was to examine and explain the influence of leadership style, work motivation and work discipline both partially and simultaneously on employee performance at the Population Control and Family Planning in South Konawe Regency. This research approach is quantitative using survey methods and explanatory research design. The data was collected by cross-section using an instrument in the form of a questionnaire. The population of this study were employees of the Population Control and Family Planning Office of South Konawe Regency, by using the method of determining respondents by census, so that the sample size was set at 84 employees. The analytical tool used is the Multivariate Regression Analysis.The results showed that the leadership style had a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Finally, leadership style, work motivation and work discipline simultaneously have a significant effect on employee performance. From the results of these studies it can be concluded that the better the leadership style is applied, the higher the work motivation of the employees and the better the level of work discipline applied by employees will be able to improve employee performance for the better.